Recent advances and challenges on enzymatic synthesis of biobased polyesters via polycondensation - Dourado Fernandes, Clara; Francisco Oechsler, Bruno; Sayer, Claudia; de Oliveira, Débora; Hermes de Araújo, Pedro H. (European polymer journal, 2022)
[Display omitted] •Systematic study of biobased building blocks for the biosynthesis of polyesters.•Challenges of polycondensation at low temperatures: Use of organic solvents.•Lipase-catalyzed policondensation reaction was systematically reviewed.•Polycondensation of aliphatic monomers: Esterification and transesterification. The attractiveness of bio-based polymers has increased in recent years, thanks to the significant development of biorefineries that allow access to a wide variety of bio-based building blocks containing oxygenated functional groups such as esters, carboxylic acids, and hydroxyls. Several of these compounds are already used in the production of aliphatic polyesters, usually at high temperatures and in the presence of metal-based catalysts. Aiming at a more sustainable process, the interest in polycondensation catalyzed by lipases has grown, because, in addition to having stereospecificity to bio-based monomers, lipases also favor polymeric synthesis at relatively low temperatures, being a strategy that allows the polymerization of unsaturated monomers. Herein, the synthesis of aliphatic polyesters by enzymatic polycondensation using bio-based building blocks was revised to provide some insights into the most promising polymers. Studies carried out in the last decade (2011–2022) were systematically examined for enzymatic polycondensation reactions by esterification and transesterification, with an emphasis on the use of bio-based monomers such as 1,3-propanediol (PDO), combined with different acids and diesters. In addition, important technical aspects such as the influence of organic solvents, methods of removing by-products, and strategies for increasing molecular weight, are elucidated providing guidelines for future researches. Therefore, this review shows feasible strategies for the synthesis of polyesters based on renewable monomers and sustainable catalysts, bringing new challenges and opportunities in this subject of scientic and industrial interest.